Pan-Cancer Analysis of the Solute Carrier Family 39 Genes in Relation to Oncogenic, Immune Infiltrating, and Therapeutic Targets - Qu, Yi-Yuan; Guo, Rong-Yan; Luo, Meng-Ling; Zhou, Quan (Frontiers in Genetics, 2021)
Background: Emerging evidence has shown the solute carrier family 39 (SLC39A) members play a significant role in oncogenic and infiltrating immune in multiple types of tumors. However, the precise relationship between SLC39A family genes and clinical prognosis and tumor cell infiltration in pan-cancer has not been fully elucidated. Methods: In our study, we investigated the expression profile, genetic mutation, prognostic effect, function enrichmen, immune infiltrating and potential therapeutic targets of SLC30A family members in pan-cancer by analyzing multiple public databases such as the Oncomine, TIMER, GEPIA, cBioPortal, KM-plotter, PrognoScan, GeneMANIA, STRING, DAVID, TIMER 2.0 and CellMiner database. Results: Compared with the normal control group, the expression levels of most SLC39 family genes in tumor tissues were significantly up-regulated. In mutation analysis, the mutation frequencies of SLC39A4 and SLC39A1 were higher among all members, 6% and 4%, respectively, and the overall mutation frequency of SLC39A family genes ranging from 0.8% to 6% in pan-cancer. Also, the function of SLC39A highly related genes was enriched in zinc II ion transport across the membrane, steroid hormone biosynthesis and chemical carcinogenesis. In immune infiltration analysis, the expression level of SLC39A family genes was notably related to the immune infiltration levels of 6 types of immune cells in specific types of tumors. In addition, SCL39A family genes were significantly related to the sensitivity or resistance of 63 anti-tumor drugs in a variety of tumor cell lines. Conclusion: These results indicate that the SLC39 family genes maybe play significant roles to determine the cancer progression, the immune infiltrating and drug sensitivity in in multiple cancers. Our study also provides novel insights for the direction of potential targets of SLC39 family genes in pan-cancer.